A Comparative Study Of Subordinating Conjunctions In English And Uzbek (Texas Journal of Multidisciplinary Studies, 2025)
This study provides a comparative analysis of subordinating conjunctions in the English and Uzbek languages, focusing on their structure, function, and usage. The research employs a qualitative content analysis approach, utilizing data from grammar books, academic articles, and online language resources. These methods allowed for a systematic and detailed examination of the subordinating conjunctions in both English and Uzbek languages. The findings reveal both similarities and differences between the subordinating conjunctions in English and Uzbek, including variations in structure and specific conjunctions used to convey relationships between clauses. These insights have implications for comparative linguistics, language teaching, and translation, as understanding the nuances of subordinating conjunctions in both languages is essential for accurate communication and effective language learning. The results highlight both the similarities and differences between the two languages, offering valuable insights for language learners, teachers, translators, and linguists. The discussion of these implications not only deepens our understanding of the linguistic features in question but also highlights potential directions for future research.